Выбор программных инструментов для компьютерных презентаций учебного назначения - Шеховцова, Виктория Ивановна; Сажко, Галина Ивановна (НТУ "ХПИ", 2016)
В статье делается обзор исследований подходов к использованию презентаций в учебных целях и предложена авторская классификация типов презентаций по принципу построения. Выделены основные технологии представления материала и дана их отличительная характеристика. Рассмотрены наиболее популярные программные продукты для создания презентаций. Даны краткие описания их инструментальных возможностей в проекции создания презентаций учебного назначения. Обозначены их преимущественные и слабые стороны для различных вариантов визуализации учебного материала. Указаны приоритетные среды для презентаций разного типа.

The article provides an overview of researches approaches to using of presentations for training purposes and is proposed authorial classification of types of presentations on the principle of constructing. Identified the main technologies of presentation of the material, given their distinctive characteristics. The authors reviewed the most popular software for creating presentations In the article are given a brief description of their instrumental abilities in the projection of creating presentations for educational purposes. Their advantageous and weaknesses were identified for different visualization options of educational material. There are identified priority to development environment for different types of presentations. The resulting classifier makes it possible to systematize information about the properties of cloud technologies for creating presentations for the understanding of the benefits and expediency of application specific web-service in the educational activity, and in the future professional activity of graduates. The proposed review of existing software products will allow to orient in a variety of proposals, and to find its own version of the visualization tool.
Select software tool for computer presentations educational purposes
Keywords: презентация; визуализация; слайд; мультимедиа; анимация; программная среда; облачный сервис; presentation; visualization; slide; multimedia; animation; software environment; cloud service